Multivariate analysis of perfume quality based on fragrance base note properties - Tengku Fazarina Tengku Ab. Ghani, 1990-, author; Hasmerya Maarof, supervisor; Mohamed Noor Hasan, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2015